Thyroid Hormone-Regulated Cardiac microRNAs are Predicted to Suppress Pathological Hypertrophic Signaling - Janssen, Rob; Zuidwijk, Marian J.; Kuster, Diederik W. D.; Muller, Alice; Simonides, Warner S. (Frontiers in Endocrinology, 2014)
Cardiomyocyte size in the healthy heart is in part determined by the level of circulating thyroid hormone (TH). Higher levels of TH induce ventricular hypertrophy, primarily in response to an increase in hemodynamic load. Normal cardiac function is maintained in this form of hypertrophy, whereas progressive contractile dysfunction is a hallmark of pathological hypertrophy. MicroRNAs (miRNAs) are important modulators of signal-transduction pathways driving adverse remodeling. Because little is known about the involvement of miRNAs in cardiac TH action and hypertrophy, we examined the miRNA expression profile of the hypertrophied left ventricle (LV) using a mouse model of TH-induced cardiac hypertrophy. C57Bl/6J mice were rendered hypothyroid by treatment with propylthiouracil and were subsequently treated for three days with TH (T3) or saline. T3-treatment increased LV weight by 38% (p<0.05). RNA was isolated from the LV and expression of 641 mouse miRNAs was determined using Taqman Megaplex arrays. Data were analyzed using RQ-manager and DataAssist. A total of 52 T3-regulated miRNAs showing a >2-fold change (p <0.05) were included in Ingenuity Pathway Analysis to predict target mRNAs involved in cardiac hypertrophy. The analysis was further restricted to proteins that have been validated as key factors in hypertrophic signal transduction in mouse models of ventricular remodeling. A total of 27 mRNAs were identified as bona fide targets. The predicted regulation of 19% of these targets indicates enhancement of physiological hypertrophy, while 56% indicates suppression of pathological remodeling. Our data suggest that cardiac TH action includes a novel level of regulation in which a unique set of TH-dependent miRNAs primarily suppresses pathological hypertrophic signaling. This may be relevant for our understanding of the progression of adverse remodeling, since cardiac TH-levels are known to decrease substantially in various forms of pathological hypertrophy.